CPT-based p-y analysis for piles embedded in clays under cyclic loading conditions - Kim, Garam; Kyung, Doohyun; Park, Donggyu; Kim, Incheol; Lee, Junhwan (KSCE journal of civil engineering, 2016)
The design of offshore mono-piles is subjected to various uncertainties more than inland cases, due to experimental difficulties in characterizing required soil parameters under offshore environment. In this study, a CPT-based p - y method is proposed for monopiles embedded in clay under cyclic loading conditions. As offshore mono-piles are particularly targeted in this study, the cyclic loading condition was introduced as an important design consideration. Based on the effective cone factor, the ultimate lateral soil resistance and p - y function were formulated as a function of CPT cone resistance and cyclic loading effect factor with consideration of the number of loading cycle. As the CPT-based p - y function utilizes the continuous CPT profile directly, detailed depth profile of soil characteristics can also be directly taken into account for the analysis without additional sampling and testing procedure. The load transfer analysis using the proposed CPT-based p - y analysis for cyclic loading condition was programmed using the discretized implementation algorithm for the beam-on-elastic foundation model. To validate the CPT-based p - y analysis method, the calculated lateral load responses were compared with the results obtained from the finite element analysis and case examples for static and cyclic loading conditions.